2021
DOI: 10.1097/ogx.0000000000000961
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Port-Site Hernia: An Underrecognized Iatrogenic Complication of Laparoscopic Surgery

Abstract: Importance: Port-site hernia is an iatrogenic complication with a documented incidence between 0.65% and 2.8%. However, the true incidence could be higher because of delayed onset, asymptomatic nature, and loss to follow-up. Port-site hernia could be further complicated by incarceration or strangulation leading to small bowel obstruction requiring emergent surgical intervention, thus imposing significant financial and emotional burden to patients.Objective: This article aims to provide a summary of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
(193 reference statements)
0
6
0
Order By: Relevance
“…1,2 A previous American Association of Gynecologic Laparoscopists surgery study of 840 portsite hernia showed that approximately 85% of cases occurred at sites >10 mm; thus, the larger port should be noted as a risk factor for port-site hernias. 2 Although the size of the trochar requiring fascial closure remains controversial, several studies have suggested a >10mm size for the closure of port sites. 2 Despite fascial closure of the port site, our case developed to port-site hernia due to the ileus.…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations
“…1,2 A previous American Association of Gynecologic Laparoscopists surgery study of 840 portsite hernia showed that approximately 85% of cases occurred at sites >10 mm; thus, the larger port should be noted as a risk factor for port-site hernias. 2 Although the size of the trochar requiring fascial closure remains controversial, several studies have suggested a >10mm size for the closure of port sites. 2 Despite fascial closure of the port site, our case developed to port-site hernia due to the ileus.…”
Section: Casementioning
confidence: 99%
“…The port‐site hernia is a potentially serious complication of minimally invasive surgery (MIS) with a reported incidence of 0.5–2% 1,2 . A previous American Association of Gynecologic Laparoscopists surgery study of 840 port‐site hernia showed that approximately 85% of cases occurred at sites >10 mm; thus, the larger port should be noted as a risk factor for port‐site hernias 2 . Although the size of the trochar requiring fascial closure remains controversial, several studies have suggested a >10‐mm size for the closure of port sites 2 …”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of TSH is unclear (2,3). Imaging such as ultrasound and CT scans appear to diagnose many more TSH than are clinically detectable, and also help clarify the diagnosis when a TSH is clinically suspected (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%